Demographic determinants of wildlife attraction selection among international return tourists in Tanzania: implications for strategic marketing - Betty Amos Begashe; Salum Matotola; John Thomas Mgonja (Cogent Business & Management, 2024)
This study examines the demographic determinants for the choice of wildlife attractions among international repeat tourists in Tanzania to provide valuable insights for destination planning and marketing. The study employed binary logistic regression analysis and cross-tabulation to assess the influence of demographic characteristics on the selection of wildlife attractions from the total 1550 international repeat tourists. The demographic attributes of tourists, including family size, employment status, income level, and region of origin, exert a substantial impact on the selection of the wildlife attraction, as indicated by a significant p-value <0.05. While individuals with medium-level annual income, retirees, students, and those individuals who are from Asia and North America are drawn to wildlife experiences. Unlike, tourists residing from small size family (less than members) and those who are coming from South America, show reduced interest in wildlife attractions. Moreover, the results from the cross-tabulation revealed that individuals with a moderate annual income, especially those who are from large family sizes, exhibit a more pronounced preference for wildlife. Additionally, the findings indicated that repeat tourists showing a higher inclination towards wildlife are individuals who are retired and have a family size exceeding three members. These findings shed light on possibilities for marketers to enhance their strategies, ensuring that information regarding the diverse range of wildlife offerings and new wildlife packages reaches individuals displaying a strong inclination for repeat visits.
Keywords: 650; Demographiccharacteristics; international tourists; repeat tourists; touristschoices; wildlifeattractions